Governança das águas na Bahia: uma análise da política estadual de recursos hídricos à luz da descentralização, da participação social e da cobrança - CERQUEIRA, Lucas Santos (2017)
Water is a public good and of common interest. It's all function and especially to ensure the State's duty to preserve your, with the development of public policies capable of guaranteeing your availability in a democratic manner and participatory. With the enactment of law 9,433/97, known as the law of waters, Brazil adopted the governance as a new form of management of water resources. Water governance in Bahia is the axis of this research and will be analyzed in the context of decentralization, social participation and recovery. Since 2006, the year of creation of the first Basin Committee in the State, by the year 2015, year end analysis of that study, Bahia presents only the creation of 14 26 RPGAS Bowl committees, the preparation of basin plans 9 and not institutionalized the collection in any of the committees. This is a descriptive-exploratory research, because the topic is still little explored in the State and is justified by the need to point out what the real situation of the water management in Bahia. In relation to methodological procedures, besides the bibliographical research, documentary research, by examining the minutes of the meetings of the committees of the State and of semi-structured interview with the responsible for water management in the INEMA. When you ask how is the water governance in the State of Bahia was concluded, on the basis of this study, there's no political interest of the State to promote the decentralization of water management, because the way you're being managed the process, even with the ANA, INEMA is the protagonist, the civil society representatives are mere supporting players and the spaces of debates, What are the Bowl committees, are figurative spaces and drained of power.